The Influence of Words of Mouth, Company Credibility, and Price on the Decision to Purchase Ship Repair Services from Shipyard Companies - Virgianti, Ima Vida; Ronny , R. (Manunggal Halim Jaya, 2025)
Consumer decision-making varies depending on the types of purchasing decisions; more complex decisions may involve more participation and greater freedom to buy. The purpose of this study was to determine the effect of word of mouth on purchase intention, the effect of word of mouth on purchase decision mediated by purchase intention, the effect of word of mouth on purchase decision, the effect of price on purchase intention, the effect of price on purchase decision mediated by purchase intention, the effect of price on purchase decision, the effect of credibility on purchase intention, the effect of credibility on purchase decision mediated by purchase intention, the effect of credibility on purchase decision and the effect of purchase intention on purchase decision. This type of research is quantitative research. The sample in this study were companies or individuals who owned ships, shipping agents, or ship management who had carried out ship repairs at PT PAL Indonesia. As many as 100 respondents used purposive sampling techniques. The analysis technique in this study used Warp Partial Least Square (Warp PLS) analysis. The results of the analysis in this study are that there is a significant influence of word of mouth on purchase intention, there is no significant influence of word of mouth on purchasing decisions mediated by purchase intention, there is a significant influence of word of mouth on purchasing decisions, there is a significant influence of price on purchasing decisions mediated by purchase intention, there is a significant influence of price on purchasing decisions, there is a significant influence of credibility on purchasing intentions, there is no significant influence of credibility on purchasing decisions mediated by purchase intention, there is a significant influence of credibility on purchasing decisions, and there is a significant influence of purchasing intentions on purchasing decisions.